2001
DOI: 10.1034/j.1600-048x.2001.320110.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of haematophagous ectoparasites on the health of nestling birds: haematocrit vs haemoglobin levels in House Wrens parasitized by blow fly larvae

Abstract: We compared haematocrits and blood haemoglobin concentrations of nestling House Wrens Troglodytes aedon in nests with relatively large numbers of haematophagous larvae of the blow fly Protocalliphora parorum (>6.4 large larvae/nestling) and nests in which exposure to larvae was severely reduced or eliminated (0–2.0 larvae/nestling). Heavily parasitized nestlings showed no reduction in haematocrit levels but a significant 28% reduction in haemoglobin levels. Previous research on avian response to chronic blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 13 publications
2
81
0
Order By: Relevance
“…This is consistent with results of other studies (e.g. Merino & Potti 1995, O'Brien et al 2001. Hence, the question arises, do parents try to reduce the effects by infestation-dependent feeding and other types of behaviour (Rothschild & Clay 1952, Johnson & Albrecht 1993, Morrison & Johnson 2002, Simon 2003?…”
Section: Introductionsupporting
confidence: 81%
“…This is consistent with results of other studies (e.g. Merino & Potti 1995, O'Brien et al 2001. Hence, the question arises, do parents try to reduce the effects by infestation-dependent feeding and other types of behaviour (Rothschild & Clay 1952, Johnson & Albrecht 1993, Morrison & Johnson 2002, Simon 2003?…”
Section: Introductionsupporting
confidence: 81%
“…It is unknown if these infestations are affecting nesting success, but effects of parasitic blood loss can include mortality, anemia, and retarded tissue growth due to reductions in hemoglobin levels and transport of oxygen to tissue (O'Conner, 1977;Gold and Dahlsten, 1983;O'Brien et al, 2001). There is no direct evidence that parasitic blood loss had an effect on the survival of these owls.…”
mentioning
confidence: 99%
“…It is likely that parasitized nestlings that are anaemic have a lower oxygen-carrying capacity, which may result in fledglings having trouble finding food and being more vulnerable to predation in their first few days after leaving the nest due to lowered flight ability and endurance (O'Brien et al 2001;Simon et al 2004). Previous studies have found that nestlings infested with various nest ectoparasites had lower haematocrit values than noninfested nestlings (Chapman 1973;Whitworth & Bennett 1992;Richner et al 1993;Simon et al 2004), although others have found no effect of parasites on haematocrit ( ).…”
Section: Haematocritmentioning
confidence: 99%